2015 53rd Annual Allerton Conference on Communication, Control, and Computing (Allerton) 2015
DOI: 10.1109/allerton.2015.7447151
|View full text |Cite
|
Sign up to set email alerts
|

Are Slepian-Wolf rates necessary for distributed parameter estimation?

Abstract: We consider a distributed parameter estimation problem, in which multiple terminals send messages related to their local observations using limited rates to a fusion center who will obtain an estimate of a parameter related to observations of all terminals. It is well known that if the transmission rates are in the Slepian-Wolf region, the fusion center can fully recover all observations and hence can construct an estimator having the same performance as that of the centralized case. One natural question is wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…Indeed, it was observed in [4,16] that a standard information-theoretic solution such as Slepian-Wolf coding may not always be the way to go, and [16] mentions the the Körner-Marton scheme in this respect. Further, Shimokawa and Amari [19] point out the possible application of the Körner-Marton scheme to distributed parameter estimation in a similar setting and a similar observation is made in [20]. However, to the best of our knowledge, the present work is the first to propose an actual Körner-Marton-based scheme for distributed hypothesis testing and to analyze its performance.…”
Section: Introductionsupporting
confidence: 68%
“…Indeed, it was observed in [4,16] that a standard information-theoretic solution such as Slepian-Wolf coding may not always be the way to go, and [16] mentions the the Körner-Marton scheme in this respect. Further, Shimokawa and Amari [19] point out the possible application of the Körner-Marton scheme to distributed parameter estimation in a similar setting and a similar observation is made in [20]. However, to the best of our knowledge, the present work is the first to propose an actual Körner-Marton-based scheme for distributed hypothesis testing and to analyze its performance.…”
Section: Introductionsupporting
confidence: 68%
“…Zhang et al [11] provided minimax lower bounds for a distributed estimation setting in which all terminals observe samples from the same distribution. El Gamal and Lai [12] showed that Slepian-Wolf rates are not necessary for distributed estimation over finite alphabets.…”
Section: Related Workmentioning
confidence: 99%
“…But it is unlikely to be achievable when the sample sets are distributed to the two processors. A recent paper of El Gamal and Lai [33] studies the problem of decentralized minimum-variance unbiased estimation of W based on observations quantized at the rate of b/n. It is shown that Slepian-Wolf rates are not necessary to achieve the centralized estimation performance, but in their protocol b needs to be proportional to n. The optimal rate region for this decentralized estimation problem is still unknown.…”
Section: B Dependent Sample Setsmentioning
confidence: 99%